Arrow's impossibility theorem: Preference diversity in a single-profile world - Allan M. Feldman; Roberto Serrano (Brown University, Department of Economics, 2007)
In this paper we provide a simple new version of Arrow's impossibility theorem, in a world with only one preference profile. This theorem relies on a new assumption of preference diversity, and we explore alternative notions of preference diversity at length.
Keywords: D60; D70; D71; 330; Arrow's theorem; single-profile; preference diversity; Unmöglichkeitstheorem; Theorie